A web-based Demand Planning System (DPS) to enable coordinated re-manufacture of automotive components. (28th October 2004) - Edwards, James; Lyons, Andrew; Kehoe, Dennis
Remanufacturing has gained popularity in recent years due to both environmental necessity and the potential for increased profits. Information systems are key to remanufacturing processes as they can reduce coordination problems and create improved visibility. This is especially important in remanufacturing as the rate of returns and/or demand for remanufactured products can be subject to heavy fluctuations. Many corporate legacy systems do not have the capacity to cope with remanufacturing circumstances and so the prototyped application discussed in this paper provides a cheap alternative to the otherwise heavy investment that would accompany a new ERP product. This paper reports on a case study involving two companies involved in the manufacture and assembly of automotive transmissions. Furthermore, it provides evidence to suggest that the internet can provide a simple and cost-effective solution to significantly improve the information flow between two companies situated in a reverse flow supply chain.